2016
DOI: 10.1039/c6cc02894b
|View full text |Cite
|
Sign up to set email alerts
|

A click chemistry-based microRNA maturation assay optimized for high-throughput screening

Abstract: Catalytic enzyme-linked click-chemistry assays (cat-ELCCA) are an emerging class of biochemical assay. Herein we report on expanding the toolkit of cat-ELCCA to include the kinetically superior inverse-electron demand Diels-Alder (IEDDA) reaction. The result is a technology with improved sensitivity and reproducibility, enabling automated high-throughput screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…For the click chemistry detection step, we chose our second-generation approach, which utilizes inverse-electron demand Diels–Alder (IEDDA) chemistry, and HRP was labeled with trans-cyclooctene (TCO). 20 We have previously demonstrated that, because of its kinetic superiority, replacing our first-generation copper-catalyzed alkyne–azide cycloaddition (CuAAC) click chemistry detection step 21,22 with IEDDA allowed us to develop a technology with improved sensitivity and reproducibility, enabling automated HTS. 20 Similar results were observed using CuAAC with PPI cat-ELCCA (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…For the click chemistry detection step, we chose our second-generation approach, which utilizes inverse-electron demand Diels–Alder (IEDDA) chemistry, and HRP was labeled with trans-cyclooctene (TCO). 20 We have previously demonstrated that, because of its kinetic superiority, replacing our first-generation copper-catalyzed alkyne–azide cycloaddition (CuAAC) click chemistry detection step 21,22 with IEDDA allowed us to develop a technology with improved sensitivity and reproducibility, enabling automated HTS. 20 Similar results were observed using CuAAC with PPI cat-ELCCA (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The scheme for cat-ELCCA for Dicer-mediated pre-miRNA maturation is shown in Fig. 2 (Garner, 2018a;Lorenz et al, 2015;Lorenz & Garner, 2016. In brief, a chemically synthesized, trans-cyclooctene (TCO)-labeled pre-miRNA substrate is first immobilized into the wells of a 384-well streptavidin-coated microtiter plate.…”
Section: Cat-elcca For Dicer-mediated Pre-mirna Maturationmentioning
confidence: 99%
“…To facilitate the discovery of new chemical entities for targeting RNAs, we have developed high-throughput screening (HTS) technology termed catalytic enzyme-linked click chemistry assay, or cat-ELCCA, which is a robust screening platform that does not suffer from compound interference (Garner, 2018a;Lorenz & Garner, 2016Lorenz, Song, & Garner, 2015;Lorenz, Vander Roest, Larsen, & Garner, 2018). Key advantages of cat-ELCCA include its increased sensitivity due to catalytic signal amplification, negligible compound interference in comparison to traditional fluorescence-based assays due to added washing steps, and HTS applicability with Z' factors >0.6 using automated liquid handling (Garner, 2018a;Garner & Janda, 2010, 2011Lorenz & Garner, 2016Lorenz, Kaur, et al, 2018;Lorenz et al, 2015;Lorenz, Vander Roest, et al, 2018;Song, Menon, Mitchell, Johnson, & Garner, 2017;Zhang, Chung, & Oldenburg, 1999). As proof of concept for RNA-targeted probe discovery, we applied cat-ELCCA toward the goal of identifying selective and RNA-binding inhibitors of Dicer-mediated microRNA (miRNA or miR) maturation ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Over the past few years, the Garner laboratory has developed high-throughput screening technology for the discovery of small molecule modulators of RNA biology, including RPIs. [43][44][45][46] Most recently, we have developed a click chemistry-mediated complementation assay, a homogeneous platform in which signal is dependent upon RPI-driven protein complementation of a split luciferase engineered from NanoLuc (NanoLuc Binary Technology; NanoBiT), allowing for catalytic signal amplification upon detection of full-length RPIs. 47 As our previously developed assay platforms were biochemical in nature, to further advance our ability to study and manipulate RNA biology, we became interested in the development of a live-cell assay for RPIs.…”
Section: Introductionmentioning
confidence: 99%